AB1065 Diagnosing gout without joint fluid aspiration: A systematic literature review using monosodium urate crystals as a reference standard. (23rd January 2014) - Sivera, F.; Andres, M.; Carmona, L.; van der Heijde, D.; Falzon, L.
Abstract : Background: The identification of MSU crystals in joints and tophi is the "gold standard" for the diagnosis of gout. Unfortunately and despite current recommendations, the search for crystals is not regularly performed [1] and many patients with gout are diagnosed on the basis of clinical and laboratory findings sometimes coupled with imaging techniques. Objectives: To evaluate the diagnostic utility of clinical, laboratory and imaging for diagnosing gout. Methods: A systematic literature search was performed in Medline, EMBASE and the Cochrane library from 1950 to October 2011 and in ACR and EULAR abstracts (2010-2011) identifying the studies on gout diagnosis. To be included, the studies had to evaluate the diagnostic value of clinical, laboratory or imaging features in gout and use MSU crystal identification as the reference standard. Titles and abstracts of the identified references were screened independently by 2 reviewers for the inclusion criteria. Subsequently, included articles were reviewed in detail and the data collected using ad hoc standard forms. A hand search was completed by reviewing the references of the included studies and all the publications or other information provided by experts were examined. Positive and negative likelihood ratios (LR) were calculated. Risk of bias was evaluated using the Cochrane tool for assessment of diagnostic tests. Results: Of the 5, 558 references retrieved, 5 papers (4 studies) fulfilled the inclusion criteria: 3 on clinical features, 1 on ultrasound (US) features and 1 on dual-energy CT (DECT). Overall risk of bias of these studies was moderate-low. Clinical and laboratory features that had a LR+ over 2.0 include: 1st MTP painful or swollen, unilateral podagra, unilateral tarsitis, presence of suspected tophi, response to colchicine, association of a cardio-vascular disease, beer consumption, hyperuricemia, serum uric acid (sUA) >7.06 (males)/5.72 (females) mg/dL, sUA >5.88 mg/dL, estimated glomerular filtration rate <60ml/min. In X-rays, the presence of asymmetric swelling and the presence of subcortical cysts in the absence of erosions both showed LR+ over 2.0. In US, the presence of the double contour sign had a LR+ of 13.63 (LR- 0.65) and punctiform deposits in the synovial membrane LR+ 2.22 (LR- 0.35). In the DECT, the detection of urate deposits in joints had a LR+ of 9.5 (LR- 0.05). Conclusions: MSU identification in a synovial fluid sample or after needling a tophus is the recommended diagnostic gold standard for gout diagnosis and should be performed whenever possible. However, some clinical, laboratory and imaging features show good LR and could be used as a diagnostic aid when MSU crystal identification is impracticable. References: Perez-Ruiz F. J Clin Rheumatol 2011; 17 (7):349. Disclosure of Interest: None Declared